Concept analysis of nurse retention. (3rd July 2019) - Efendi, Ferry; Kurniati, Anna; Bushy, Angeline; Gunawan, Joko
Abstract: Nurse retention is widely acknowledged as a crucial international workforce issue, yet the concept remains ambiguous. This study focuses on a concept analysis in an effort to clarify the attributes of nurse retention, including its antecedents and consequences. The Walker and Avant approach was applied to analyze the concept of nurse retention. Four key attributes of nurse retention were identified in the analysis, specifically motivation, intention, and individual decision; strategy and intervention; geographic context; and attachment to work. Antecedents of nurse retention included the healthcare system at the macro level, the health care facility, health personnel, and living conditions. Retention has consequences for individual nurses, the healthcare organization, and the overall health system. Our concept analysis provides clarification to better understand nurse retention along with its implications for the healthcare workforce. The analysis further emphasizes the importance of retention as a comprehensive priority issue for human resources when recruiting and maintaining the nursing workforce internationally.